Association of elevated plasma CCL5 levels with high risk for tic disorders in children - You, Hai-zhen; Zhang, Jie; Du, Yaning; Yu, Ping-bo; Li, Lei; Xie, Jing; Mi, Yunhui; Hou, Zhaoyuan; Yang, Xiao-Dong; Sun, Ke-Xing (Frontiers in Pediatrics, 2023)
Abnormal levels of some peripheral cytokines have been reported in children patients with tic disorders (TDs), but none of these cytokines can be a biomarker for this disease. Our aim was to systemically profile differentially expressed cytokines (DECs) in the blood of TD patients, examine their associations with TD development, and identify from them potential biomarkers for the prediction and management of the risk for TDs. In this study, a cytokine array capable of measuring 105 cytokines was used to screen for DECs in the plasma from 53 comorbidity-free and drug-naïve TD patients and 37 age-matched healthy controls. DECs were verified by ELISA and their associations with TD development were evaluated by binary logistic regression analysis. Elevation of a set of cytokines was observed in TD patients compared with controls, including previously uncharacterized CCL5, Serpin E1, Thrombospondin-1, MIF, PDGF-AA, and PDGF-AB/BB. Further analysis of DECs revealed a significant association of elevated CCL5 with TD development (p=0.005) and a significant ROC curve for CCL5 as a risk factor (AUC 0.801 [95%CI, 0.707-0.895], P <0.0001). Conclusion: This study identified and validated a previously uncharacterized cytokine CCL5 as a major DEC in the plasma of TD patients and showed that plasma CCL5 has potential to be a risk factor for TD development that could be used as an auxiliary diagnostic biomarker for this disease.